(untitled) (Revista Portuguesa de Medicina Geral e Familiar, 2024)
Hereditary angioedema (HAE) is a rare, hereditary disease and its manifestations may be life-threatening. It differs from histaminergic angioedema since it shows different underlying mechanisms and, therefore, does not respond to antihistamine or adrenaline treatment. The authors present a case of hereditary angioedema to highlight the importance of prompt referral to the allergy and clinical immunology for further evaluation and correct diagnosis in case of suspicion of this entity.